Da enxada à colher de pedreiro: trajetórias de vulnerabilidade social na construção civil - Cockell, Fernanda Flavia (Universidade Federal de São Carlos, 2008)
The research has as objective to study the occupational trajectories of unstable workers of construction industry that face a permanent social vulnerability. We tried to analyze the type of strategies and social networks used by these unstable workers, through the insecurity of employment contracts and the absence of social State protection or in front of some difficult to obtain formal protection. We examine how they deal with the social and natural events like employee job search, unemployment, unstable income, ageing and absence from work caused by work-related accidents and illness and how they appealed to informal social networks to solve these specific situations. We also analyze the workers perceptions of how this circumstance affects their working conditions, their health and their social reproduction. For this, we interviewed twenty civil building laborers of São Carlos-SP, Brazil, with at least twenty-five years old and five years working as a buildings laborer. We choice this sector because of its high instability, large informal contingent, outsourcing and subcontracted workers, high turnover, harmful working conditions and insecurity of employment contracts. The qualitative analysis shows that construction industry, that have been historically an employment choice for young rural migrants, newly unemployed person and workers without experience, becomes a job opportunity (or the last choice) for retirements and specialized labor force, dismissed of heavy industry during the process of productive restructuring. Some of them, who already had experimented labor and social security laws, starts to work in a social and economic precarious situation after set to work in construction industry, such as metal workers. We identified that informal social networks are crucial for professional vulnerability, job inconstancy and absence from work, at long last, in the daily survival. The most important social networks are the nuclear family, blood ties, communal identity and religious identification. The state is increasingly less present and the non-state public institutions, such as the union, are not part of these work s networks. The workers don t have financial conditions to acquire private forms of protection and in front of the life instability, they build strategies such as double day of work, pin money, purchasing goods profitable, and, in some cases, they need to continue working after retirement. The vulnerability present along all trajectories, make workers notes their condition with powerlessness, revolt and resignation.
Keywords: Estrutura social; Redes sociais; Vulnerabilidade social; Construção civil; São Carlos metalúrgicos; ENGENHARIAS::ENGENHARIA DE PRODUCAO